Economic returns on investing in early childhood development in Vietnam: a cost-benefit analysis - Baek, Yeji; Fisher, Jane; Tran, Thach; Owen, Alice; Nguyen, Trang; Luchters, Stanley; Hipgrave, David B.; Hanieh, Sarah; Tran, Tuan; Ha, Tran-Thi-Thu; Biggs, Beverley-Ann; Ademi, Zanfina (BMC health services research, 2025)
Economic evidence on the long-term benefits of investing in early childhood development is limited. This study aimed to estimate the potential long-term economic benefits of an early childhood development intervention 'Learning Clubs' in Vietnam. We conducted a cost-benefit analysis to estimate the costs and benefits of the intervention compared to the standard of care from a limited societal perspective. The intervention cost and child cognitive development outcome were derived from the published 'Learning Clubs' trial-based cost-effectiveness analysis. Benefits were monetised based on the gains in wages associated with improved cognitive development over a lifetime at the population level, using a life-table model. The benefit-cost ratio was estimated as the benefits in wages divided by the intervention cost with a 3% discount rate, assuming nationwide scale up to a hypothetical national birth cohort. Sensitivity, scenario, and threshold analyses were conducted to examine the uncertainty around the model. The benefit-cost ratio was 5.52, indicating that the expected benefit for each US$1 invested would be US$5.52. The intervention would generate economic benefits of US$1,566 per child over their lifetime. Upon nationwide scale-up, the total benefit would amount to US$2.28 billion per national annual birth cohort. Probabilistic sensitivity analyses estimated the benefit-cost ratio to be 5.90 (95%CI 2.66 to 11.12). The findings were relatively robust as the benefit-cost ratios remained above 1 in all sensitivity and scenario analyses. Our findings support greater investments in early childhood development. The Excel-based model is available for further use and adaption to other settings.